2009
DOI: 10.1177/0022343309102659
|View full text |Cite
|
Sign up to set email alerts
|

Civil Conflict and Displacement: Village-Level Determinants of Forced Migration in Aceh

Abstract: The purpose of this paper is to identify the determinants of displacement behavior based on various push and pull factors at the village level. The study concentrates on changes in village population during three years of civil conflict (1999)(2000)(2001)(2002) in Aceh, Indonesia. We use data on around 5200 Acehnese villages from two rounds of the Indonesian Village Potential Census (PODES) and relate village level population change to conflict variables and traditional determinants of migration. After control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 6 publications
(9 reference statements)
4
82
0
Order By: Relevance
“…These results are very interesting as they stress that both socio-economic factors and violence incidence are playing an important role in explaining household migration in rural areas of Colombia. Although similar results have been found by Engel and Ibanez (2007) and Czaika and Kis-Katos (2009), what is particularly interesting in our context is that the households of our sample are extremely poor, such that migration decisions are likely to be severely liquidity constrained. In this context, we find that receiving welfare benefits such as conditional cash transfers of the FA programme discourages household migration only if violence incidence is not unduly high.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are very interesting as they stress that both socio-economic factors and violence incidence are playing an important role in explaining household migration in rural areas of Colombia. Although similar results have been found by Engel and Ibanez (2007) and Czaika and Kis-Katos (2009), what is particularly interesting in our context is that the households of our sample are extremely poor, such that migration decisions are likely to be severely liquidity constrained. In this context, we find that receiving welfare benefits such as conditional cash transfers of the FA programme discourages household migration only if violence incidence is not unduly high.…”
Section: Discussionsupporting
confidence: 88%
“…However, there has been a growing attention paid to the consequences of civil conflicts on displacement and asylum seekers (see for example Azam and Hoeffler, 2002, Hatton, 2004, or Czaika and Kis-Katos, 2009 Giorgi, 2009). As in the first two years of the programme, the programme was not implemented everywhere (340,000 households were registered to participate in 622 municipalities of Colombia), one can easily understand that being exposed to the programme may discourage migration of the very poor households eligible for it.…”
Section: Literature On Migration and Displacementmentioning
confidence: 99%
“…It should also be noted that in many cases IDPs would have some control over where to move within their countries, and, where possible, they would choose destinations offering better opportunities for the fulfilment of basic needs as well as finding a job (Czaika and Kis-Katos, 2009;Lozano-Gracia et al, 2010). From a technical point of view, such self-selection is not an issue if one compares the labour market outcomes of IDPs with those of hosts within the same area.…”
Section: H6: Displaced Women Have Inferior Long-term Labour Market Oumentioning
confidence: 99%
“…Previous studies have found that long-term instability and violence often bring about migration and produce significant displacement, both within and across national borders (Bohra-Mishra and Massey 2011;Castles 2003;Czaika and Kis-Katos 2009;Engel and Ibânez 2007;Morrison 1993;Tolnay and Beck 1992;Williams et al 2012;Williams 2013). Threat of harm has been the most commonly cited reason for this migration (Bohra-Mishra and Massey 2011; Engel and Ibânez 2007;Williams et al 2012).…”
Section: Migration and The Unrest In Prior Researchmentioning
confidence: 99%
“…The ongoing havoc that threatens people's well-being and gives them a sense of insecurity may drive them to move out. While in other contexts, investigators have found that long-term instability and violence often beget migration (Bohra-Mishra and Massey 2011;Castles 2003;Czaika and Kis-Katos 2009;Engel and Ibânez 2007;Morrison 1993;Tolnay and Beck 1992), in the case of the southernmost Thailand, the extent to which the experience of violence has affected movement out of the southernmost provinces is still unclear.…”
Section: Migration and The Unrest In The Three Southernmost Provincesmentioning
confidence: 99%